Solar Power System: Dual-Axis Tracker & Monitoring System for a Gateway Station using Arduino & NodeMCU - Shamsuddin, Muhamad Khairi Azizi; Mohd Shah, Nor Shahida; Saparudin, Faiz Asraf; Mohd Redzuan, Ahmad Afif Aiman; Noor Azeb, Muhammad Mirza Amsyar (Progress in Engineering Application and Technology, 2021)
Sunlight is a non-disappearing and atmospheric-free source of renewable energy. The disadvantage of solar energy, however, it relies precisely on the strength of the sun. In order to create the utmost amount of energy, the solar panel has to be perpendicular to the source of light. When the photovoltaic panel is perpendicular to the sun, the solar energy conversion efficiency increases. Therefore, the purpose of this study is to propose an innovative method of tracking the sun using a resistor dependent on light (LDR). It is rational to conclude that the sun position indicates the points of the brightest region in the sky. The sun central location data is sent to the embedded processor to power two servo motors that can move both horizontally and vertically to track the sunlight. The IoT is used in this study purposely for monitoring the performance of the solar power system and the dual-axis solar tracker. The data helps to make the decision to plan operations, repairs, and preventive maintenance.